2021
DOI: 10.3892/or.2021.8033
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine inhibits ovarian cancer cell viability and promotes apoptosis by regulating the ERK/JNK signaling pathway via p38MAPK

Abstract: Ovarian cancer displays the highest mortality rate among all types of gynecological cancer worldwide. The survival of patients with ovarian cancer remains poor due to poor responses to anticancer treatments. The present study aimed to investigate the therapeutic effects and potential mechanism underlying matrine in ovarian cancer tissues, ovarian cancer cells and a CAOV-3-derived tumor-bearing mouse model. MTT, migration, invasion, flow cytometry, immunofluorescence and immunohistochemistry assays were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recent studies confirmed the antineoplasm effect of matrine on MCF-7 breast cancer and A549 non-small cell lung cancer cell lines by inhibiting AKT/mTOR axis [38,39]. Additionally, it reduced tumor growth of ovarian cancer cells in vivo by inducing the expression of ERK and JNK (c-Jun N-terminal kinase) pathways [40]. Matrine 30 also exerted a significant effect in drug-resistant tumors by inducing apoptosis and inhibiting efflux-pump activity [41,42].…”
Section: 6-naphthyridine Derivativesmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies confirmed the antineoplasm effect of matrine on MCF-7 breast cancer and A549 non-small cell lung cancer cell lines by inhibiting AKT/mTOR axis [38,39]. Additionally, it reduced tumor growth of ovarian cancer cells in vivo by inducing the expression of ERK and JNK (c-Jun N-terminal kinase) pathways [40]. Matrine 30 also exerted a significant effect in drug-resistant tumors by inducing apoptosis and inhibiting efflux-pump activity [41,42].…”
Section: 6-naphthyridine Derivativesmentioning
confidence: 93%
“…They were documented to induce apoptosis in cancer cells in both p53-dependent and p53-independent manner [23,25,148,167]. Moreover, the compounds interfere with procytotoxic signaling pathways, i.a., AKT/mTOR, ERK, JNK, WNT [38][39][40]62]. Antineoplasm properties against drug-resistant tumors could be elucidated by inhibiting efflux-pumps activity, however, this topic requires further study [41,42].…”
Section: Naphthyridines Molecular Mechanisms Of Action-what Do We Know?mentioning
confidence: 99%
“…Xin et al 116 found that matrine significantly inhibited the viability, migration and invasion of ovarian cancer cells, and induced apoptosis. In addition, matrine treatment significantly upregulated the expression levels of p38MAPK, p-ERK/ERK, and p-JNK/JNK, while p38MAPK knockdown significantly downregulated the expression levels of p-ERK/ERK and p-JNK/JNK, promoting the viability, migration and invasion of ovarian cancer cells.…”
Section: Matrine Exerts Pharmacological Effects Through the Mapk Sign...mentioning
confidence: 99%
“…The main component of Sophora flavescens preparations is matrine, which has broad pharmacological properties, including sedation, analgesia (9), antiviral (10), anti-inflammatory (11), antifibrotic (12) antitumor and immunoregulatory activity (13,14), as well as other effects (15). Previous studies have investigated the inhibitory effects of matrine on a variety of tumor cells including cervical cancer (16)(17)(18)(19)(20). Matrine combined with chemotherapy drugs, such as cisplatin, docetaxel and adriamycin, may have antitumor activity (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%